A Case of One-Stage Treatment for Six Cerebral Aneurysms of One Carotid Basin with Concomitant Occlusion of the Contralateral Internal Carotid Artery - D. V. Litvinenko; G. K. Yenaldiev; I. N. Sever; V. V. Tkachev; V. A. Porkhanov (Неотложная медицинская помощь)
We present a clinical case of successful one-stage treatment of a patient with six cerebral aneurysms of one carotid basin with concomitant chronic occlusion of the contralateral internal carotid artery. The role of hemodynamics in the pathogenesis of brain aneurysms, as well as methods and stages of surgical treatment of patients with multiple aneurysms are discussed.